Caught! Crystal trapping of a side-on peroxo bound to Cr(iv). Issue 14 (13th January 2015) - de Sousa, David P.; Bigelow, Jennifer O.; Sundberg, Jonas; Que, Lawrence; McKenzie, Christine J.
Abstract : A Cr(iv )η 2 –peroxo complex is a likely intermediate in catalytic disproportionation of H2 O2 in solution – and solid state. Abstract : A Cr(iv )η 2 –peroxo complex crystallizes from 33% aqueous H2 O2 . The complex is a likely intermediate in catalytic disproportionation of H2 O2 proposed to occur through a single metal site mechanism in solution – and solid state.